Visual Evoked Potential Findings in Road Drilling Machine laborers - Sarzaeim, Fatemeh; Hashemzehi, Mahboubeh; Shushtarian, Seyed Mohammad Masoud; Shojaei, Ahmad (Journal of Ophthalmology and Research, 2022)
Purpose: Road drilling machine laborers are exposed to heavy vibration. Vibration may affect different organs of body. The aim of present work is to look for possible effect of vibration on visual pathway of these subjects using visual evoked potential. Patients and methods: Twelve male laborers (24 eyes) were selected for the purpose of present study. The age range of the laborers was in between 25-35 years. They had normal visual acuity. They were tested for visual evoked potential (VEP). Latency (msec) and amplitude (µv) of VEP, P100 peak were recorded for all subjects and 12 age and sex matched control laborers not encountered with vibration. Result: The mean age was 30.67 ±3.47 and 30.58±3.45 in the case and control groups, respectively. the mean BCVA was 10/10 is both groups. The mean latency was 103.58± 5.24 and 98.58±2.92 and in case of amplitude it was 7.67±1.93 and 7.75±1.36 in case and Control groups respectively. There was a statistically significant higher latency of visual evoked potential P100 peak in the case compared to control groups (p>0.001). No significant difference regarding the amplitude of VEP, P100 peak was observed between two groups (P = 0.863). Conclusion: Occupational vibration in road drilling machine might have adverse effect on visual system mainly visual pathway causing increased latency of VEP, P100 Peak measured using visual evoked potentials.